A Review: The Effect of Initial Dye Concentration and Contact Time on The Process of Dye Adsorption using Agricultural Wastes Adsorbent - Oetjik, Wahyunirahma; Ibrahim, Siti Aida (Progress in Engineering Application and Technology, 2021)
Activated carbon has been extensively studied in the past due to its various applications including removal of dyes from wastewater by adsorption process. Due to that, the aim of this present study is to review the preparation method of several agricultural wastes-based activated carbon and the parameters influenced the dye adsorption efficiency in batch experiment. Journals and articles sourced from Elsevier, ScienceDirect, Google Scholar etc. that study the effect of initial dye concentration and contact time on the percentage removal % and adsorption capacity of methylene blue by agricultural waste adsorbent (coconut shell, ackee apple pod, fig (ficus carica) bast and coconut leaf) are chosen to be reviewed. The percentage removal % exhibited a decrement corresponds to the increase in initial concentration of dye and the higher the initial concentration needed longer contact time to reach equilibrium condition. The isotherm model that fitted to adsorption data reported in the reviewed research is Langmuir isotherm.